A Rare Case of Aplastic Anemia in Toxic Typhoid Fever - NOVITA, MUTIARA PUTRI NOVITA; Zaimatuddunia, Irma (Nusantara Medical Science Journal, 2024)
Introduction and importance: Typhoid fever is one of the representative febrile diseases in the tropics, with unhygienic environmental conditions and poor public health systems. Pancytopenia from hemophagocytic lymphohistiocytosis is a rare complication of typhoid fever, which may be fatal if untreated. Presentation of case: A 20-year-old woman presented to our tertiary care center with high-grade fever, body pain, and slurring of speech. Investigations showed pancytopenia, TUBEX IgM Salmonella test positive, lymphadenopathy, and peripheral blood smear showed aplastic anemia after ruling out other possibilities and diagnostics. The patient responded to culture-sensitive antibiotics, steroids, and supportive care. Discussion: Pancytopenia in typhoid fever patients is linked to the mechanism of HLH (Hemophagocytic lymphohistiocytosis). Conclusion: It is essential to diagnose and treat toxic typhoid fever with an appropriate antibiotic to prevent complications.